Stages and Patterns of Internationalization of the Chinese-Owned Firms: Market-Seeking versus Resource-Seeking Firms - Curci, Roberto; Ling-Yee, Esther; Mackoy, Robert (Journal of Comparative International Management, 2014)
This study compares and contrasts Chinese firms with internationally active value chains that started their internationalization efforts by engaging in international revenue generation or downstream value chain activities (defined as market-seeking firms) versus those that began through international sourcing or upstream value chain activities (defined as resource-seeking firms). Face-to-face survey interviews conducted with firm managers during the autumn of 2011 yielded complete data for 308 Chinese firms. Our findings suggest firms that start their internationalization process by engaging in “market-seeking” behavior showcase better performance than those that begin by engaging in “resource-seeking” activities. In addition, financial indicators are found to be strong factors that discriminate between market-seeking and resource-seeking Chinese firms.